THE INFLUENCE OF VALUE CLARIFICATION TECHNIQUE (VCT) ON STUDENTS’ DISCIPLINE ON CIVIC LEARNING AT GRADE IV SD NEGERI KALIASIN III - Putri Awaliah; Damanhuri; Ikman Nurahman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to determine the influence of the Value Clarification Technique (VCT) on students’ discipline in learning civic education at grade IV. The method of this research was a Quasi Experiment conducted in two classes, namely the experimental class and the control class. Class IV A, as the experimental class, consisted of 30 students, and Class IV B, as the control class, also consisted of 30 students. Based on the research conducted, it was revealed that there was a significant influence of the implementation of the Value Clarification Technique (VCT) on students’ discipline in the civic subject. The results of the discipline questionnaire for the VCT model obtained a score of 84.63, whereas the results of the discipline questionnaire for the lecture method were 65.23. Moreover, based on the results of the t-test in which 0.000 < 0.05, it was concluded that there was an effect of the Value Clarification Technique (VCT) method on students’ discipline and that the use of the Value Clarification Technique (VCT) method was better than the lecture method.